Knockout and humanized mice as suitable tools to identify enzymes metabolizing the human carcinogen aristolochic acid - Stiborová, Marie; Frei, Eva; Arlt, Volker M; Schmeiser, Heinz H (Xenobiotica; the fate of foreign compounds in biological systems, 2014)
UNLABELLED: 1. Aristolochic acid I (AAI) is the predominant component in plant extract of Aristolochia genus that is involved in development of aristolochic acid nephropathy, Balkan endemic nephropathy and urothelial cancer. The diseases do not develop in all individuals exposed to AAI and patients exhibit different clinical outcomes. Differences in the activities of enzymes catalyzing the metabolism of AAI might be one of the reasons for this individual susceptibility. 2. Understanding which human enzymes are involved in reductive activation of AAI generating AAI-DNA adducts, and/or its detoxication to the O-demethylated metabolite, aristolochic acid Ia (AAIa), is necessary in the assessment of the susceptibility to this compound. 3. This review summarizes the results of the latest studies utilizing genetically engineered mouse models to identify which human and rodent enzymes catalyze the reductive activation of AAI to AAI-DNA adducts and its oxidative detoxication to AAIa in vivo. 4. The use of hepatic cytochrome P450 (Cyp) reductase null (HRN) mice, in which NADPH:Cyp oxidoreductase (Por) is deleted in hepatocytes, Cyp1a1((-/-)), Cyp1a2((-/-)) single-knockout, Cyp1a1/1a2((-/-)) double-knockout and CYP1A-humanized mice revealed that mouse and human CYP1A1 and 1A2, besides mouse NAD(P)H: quinone oxidoreductase, were involved in the activation of AAI but CYP1A1 and 1A2 also oxidatively detoxified AAI.
Keywords: Cytochrome P-450 CYP1A2; Kidney Diseases; adukty DNA; Mice, Knockout; Inactivation, Metabolic; Enzymes; Cytochrome P-450 CYP1A1; metabolická inaktivace; enzymy; cytochrom P-450 CYP1A1; nemoci ledvin; Enzyme Inhibitors; Aristolochic Acids; myši knockoutované; cytochrom P-450 CYP1A2; kyseliny aristolochové; NAD(P)H dehydrogenasa (chinon); Animals; lidé; Carcinogens; NADPH-Ferrihemoprotein Reductase; karcinogeny; Humans; zvířata; DNA Adducts; myši; NADPH-cytochrom c-reduktasa; Mice; NAD(P)H Dehydrogenase (Quinone); inhibitory enzymů